O Grotesco na Dramaturgia de Ariano Suassuna - Telles, Narciso (Latin American Theatre Review, 2002)
Ariano Suassuna is one of the most important Brazilian playwrights. His works recreate the Northeastern imagination, his cultural universe and his way of looking at the world. This article analyzes the comical elements present in the plays Farsa da Boa Preguiça (1960) and O Auto da Compadecida (1955) by Ariano Suassuna. The intention is to show the complexity of these dramatic productions and their links to a popular comical tradition. (NT, in Portuguese)